Trends in the improvement of methods and equipment for the assessment of flax raw material (review) - N. S. Shimanskaya; I. V. Uschapovsky; S. V. Prokofiev (Аграрная наука Евро-Северо-Востока, 2020)
The article provides the results of the analysis of methods and instrument equipment for the assessment of quality parameters of retted flax straw and flax fiber. The traditional methods and equipment are presented. The devices developed for flax fiber quality testing used in the Russian Federation, the Republic of Belarus and Ukraine are described. Methods, equipment and modern technologies used to determine the quality of flax fiber in European countries, Canada and the United States are provided. The role of modern developments to improve the efficiency of flax production is noted. Promising methods and devices for determining the main quality indicators are identified. The use of the method of automated forecasting of technological value of fiber flax stalks makes it possible to conduct a comprehensive quality assessment based on morphological and anatomical analysis. Modern capabilities of electronic scanning microscopy provide the control of the chemical composition and structural elements of flax stems at various stages of growth and development, as well as during maceration. The use of infrared spectrometry provides high accuracy in determining humidity, strength, fiber content, and long fiber yield.However, along with high-precision equipment, there is the need for equipment and devices that allow determining the main technological indicators in the field with minimal labor, time and money costs. Research in this direction was previously carried out at the All-Russian Scientific Research Institute of Bast Crops Processing and in Kostroma State Technological University. However, the developments of the scientists were not tested in the production process and were not mass-produced. High speed and objective measurement methods will provide the accurate indicators during the process of maceration and primary processing of retted straw that will increase the technological value and competitiveness of flax fiber.